The kinase inhibitor dasatinib induces apoptosis in chronic lymphocytic leukemia cells in vitro with preference for a subgroup of patients with unmutated IgVH genes - Aditya Veldurthy; Michaela Patz; Susanne Hagist; Christian P. Pallasch; Clemens‐Martin Wendtner; Michael Hallek; Günter Krause (2008)
Abstract Src family kinases (SFKs) were described to be overexpressed in chronic lymphocytic leukemia (CLL). We wished to examine the effects of the Src and Abl kinase inhibitor dasatinib on the intracellular signaling and survival of CLL cells. Dasa-tinib showed a dose- and time-dependent reduction of global tyrosine phosphorylation and of activating phosphotyrosine levels of SFKs. Treatment with 100 nM dasatinib led to decreased levels of the activated, phosphorylated forms of Akt, Erk1/2, and p38, and induced PARP cleavage through caspase activity. In Mec1 and JVM-3 cell lines, dasatinib increased p53 protein levels and inhibited proliferation. In freshly isolated CLL cells, dasatinib reduced the expression of Mcl-1 and Bcl-xL. Combination of 5 μM dasatinib and fludarabine increased the apoptosis induction of each by approximately 50%. In 15 primary CLL samples, cells with unmutated immunoglobulin variable heavy chain (IgVH) genes were more sensitive to dasatinib than those with mutated IgVH genes (P = .002). In summary, dasatinib shows potent inhibitory effects on the survival of CLL cells in vitro, most prominently in samples obtained from patients with unfavorable prognostic features.